1982
DOI: 10.1136/bmj.285.6336.168
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after surgical correction of tetralogy of Fallot.

Abstract: not differ significantly between those patients who had taken nonsteroidal anti-inflammatory drugs (20 out of 22; 91 %) and those who had not (33 out of 48; 69%). The relative frequency of consumption of individual non-steroidal anti-inflammatory drugs did not differ between the patients with stricture and the controls (table), and ibuprofen, indomethacin, and aspirin were the drugs most often used by both groups. DiscussionWe found an association between prior consumption of non-steroidal anti-inflammatory dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 6 publications
2
16
2
Order By: Relevance
“…2,7,11 Surgical repair of TOF has a low perioperative mortality, and survivors are much improved symptomatically and are able to cope adequately with demands of pregnancy. 8 In a review of 58 pregnancies in 41 women with repaired TOF, Singh et al 8 reported that pregnancy outcome for both mother and fetus is greatly improved with surgical correction prior to pregnancy: these authors reported a live birth rate of 78% versus 33%, maternal mortality 0% versus 4% to 12%, and rate of congestive cardiac failure 2% versus 40%. In a study of 9 pregnancies in patients with TOF reported by Shime et al, 4 7 had undergone prior corrective surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2,7,11 Surgical repair of TOF has a low perioperative mortality, and survivors are much improved symptomatically and are able to cope adequately with demands of pregnancy. 8 In a review of 58 pregnancies in 41 women with repaired TOF, Singh et al 8 reported that pregnancy outcome for both mother and fetus is greatly improved with surgical correction prior to pregnancy: these authors reported a live birth rate of 78% versus 33%, maternal mortality 0% versus 4% to 12%, and rate of congestive cardiac failure 2% versus 40%. In a study of 9 pregnancies in patients with TOF reported by Shime et al, 4 7 had undergone prior corrective surgery.…”
Section: Discussionmentioning
confidence: 97%
“…3 The potential predictors of maternal morbidity include functional class, ventricular dysfunction, significant arrhythmias, cyanosis, severe outflow tract obstruction, pulmonary hypertension, and need for anticoagulation. 3,7 Pregnancy in corrected TOF is comparable to that in the general population, 8,9 but each patient needs to be individually assessed for the ability to tolerate hemodynamic changes during pregnancy. Corrective cardiac surgery improves both maternal and perinatal outcome by improving hemodynamic parameters, improving placental perfusion, and reducing the likelihood of cardiac complications.…”
Section: Discussionmentioning
confidence: 98%
“…Singh et al . reviewed 40 pregnancies in 27 women with surgically corrected TOF and reported good maternal and perinatal outcome 13 …”
Section: Pregnancy Outcomementioning
confidence: 99%
“…Previously published series have demonstrated little or no risk to the mother with a repaired TOF. Singh et al (9) reported 40 successful pregnancies in 27 women, with no adverse maternal cardiovascular events. Similarly, Nissenkorn et al (12) demonstrated no maternal complications in five women who had nine pregnancies, and the authors stressed the importance of alleviating a significant residual hemodynamic burden before pregnancy.…”
mentioning
confidence: 98%